A new subspecies of wheat: Triticum dicoccon (Schrank) Schuebl. subsp. nudicoccon Kobyl. et Smekal. - Т. N. Smekalova; V. D. Kobylyansky (Труды по прикладной ботанике, генетике и селекции, 2020)
In recent years, an increased interest in emmer wheat (Triticum dicoccon Schrank) has been observed, due to the dietary value of its grain, which is used for making highquality cereal products. The main disadvantages of this crop are a relatively low yield, if compared with other wheat species, a brittle ear, and problems with grain threshability (filmy kernels are threshed out of the ear together with the chaff). Thus, developing hulless cultivars of emmer is at present an urgent task. Constant lines of naked emmer wheat, which make up the described subspecies, served as the material for this research, including four lines developed at VIR by A. F. Merezhko and seven by V. D. Kobylyansky. The wheat produced from interspecific crosses between different varieties of the hulless T. durum Desf. and various local forms of the hulled T. dicoccon (Schrank) Schuebl. has deserved the rank of subspecies (T. dicoccon (Schrank) Schuebl. subsp. nudicoccon Kobyl. et Smekal.). The obtained hulless wheat demonstrates morphological features characteristic of T. dicoccon: its ear is flat, there are two grains in the spikelet, etc., while its kernels are easily separated from chaff.